Anti-diabetic Attributes of Desert Plant Retama: A Mini Review on its Traditional Uses and Potential Chemical Constituents - Elodemi, Mahmoud; Siddiqua, Ayesha; Seyed, Mohaamed Ali (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Diabetes mellitus (DM) is a fast-growing metabolic disorder, which affect millions around the world mostly people from developing nations. The rise of diabetes is further set to rise more in the coming years in all inhabited continents of the world. DM mainly attributed for food and lifestyle changes, less or no physical activity, obese, overweight, and major socioeconomic changes. In recent years, herbal medicine is incredibly growing because many natural products exhibit less or no side effects. It is well-established that nature-derived products protect β-cells and decrease blood glucose. AIM: We aimed to explain anti-diabetic attributes, traditional uses, and potential chemical constituents of desert plant retama. RESULTS: Numerous previous studies support the use of plant derived bioactive substances for human and animal disease therapy and reinforce their importance as a potential source of novel drug candidates. In this line a flowering bush, belong to the genus “Retama” (Fabaceae) are in use of conventional remedy in the Mediterranean basin for various diseases including DM. This potential plant genus has a great medical and socioeconomic importance and provides crucial evidence for its anti-diabetic therapeutic potential. The present review collected various documented information using the following searching engines such as PubMed, Science direct, and Google scholar. We limit our search only to English written documents for the last few decades until date. For data mining, the following MeSH words used in the databases: Retama, diabetes, phytoconstituents, pharmacological potential, anti-diabetic, insulin, in vivo, and in vitro. CONCLUSION: The outcome of this review may set new prospects for the DM patients, along with other standard medication and provide an overall insight to the well-being at the regional and global level.